The Effect of Service Quality and Social Media Promotion on Consumer Purchase Decisions at Potatoes Project Coffee Shop - Rizkisahbani, Moh; Bempah, Irwan; Mustafa, Ramlan (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the partial and simultaneous effects of service quality and social media promotion on consumer purchase decisions at Coffee Shop Potatoes Project. The research was conducted from September to December 2025 with a sample size of 43 respondents determined using Cochran's formula through non-probability sampling with accidental sampling technique. Data collection was conducted through the distribution of questionnaires directly to respondents, while data analysis used multiple linear regression. The results show that (1) service quality has a significant positive effect on consumer purchasing decisions, namely 3.783 > t-table 2.021 with a sig. value of 0.001 < 0.05 (2) social media promotion has a significant positive effect on purchasing decisions, namely 2.290 > t-table 2.021 with a sig. value of 0.027 < 0.05, and (3) service quality and social media promotion simultaneously have a significant positive effect on consumer purchasing decisions, namely 35.353 > F-table 3.232 with a sig. value of 0.000 < 0.05. The coefficient of determination value shows that 63.90% of purchasing decisions can be explained by service quality and social media promotion, while the remaining 36.10% is influenced by other variables outside the variables studied in this research.